SPIRITUAL SPACE OF SOCIETY: SOCIO-PHILOSOPHICAL ASPECT - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article discusses the spiritual space as part of the category of social space, social and philosophical aspects of the conditions and mechanisms of its formation and development, the impact on modern all-Ukrainian public processes.